The Influence of Motivation, Discipline, and Job Satisfaction on the Work Performance of Employees at the Secretariat of State for Transport, Equipment, and Communications in Dili, Timor-Leste - Santos, Longuinhos dos (Journal Research of Social Science, Economics, and Management, 2025)
The aim of the research was to observe the extent to which motivation, discipline, and job satisfaction affect employee job performance at the Secretariat of State for Transport, Equipment, and Communications in Dili. Data was collected using a questionnaire method that was delivered to 50 respondents, while only 45 respondents from the Secretariat of State for Transport, Equipment and Communications in Dili were obtained using the saturation sampling technique, in which all elements of the population became the sample. Data was processed using multiple regression. The results showed that there is a positive and significant effect of motivation on job performance, while the discipline variable does not have a significant effect on job performance because employees’ job discipline tends to be more rule-based than awareness-based. Furthermore, the researcher examined the hypothesis that job satisfaction has a positive effect on employee performance. The determination coefficient (R²) provides a significant contribution to job performance. Job performance influenced by other factors accounts for one-third of total job performance. The results indicate that Fcountand Ftablestate that there is an acceptable effect between the variables of motivation, discipline, and job satisfaction on job performance. According to the research limitations, future researchers who conduct similar research should use more samples and determine performance that is appropriate to the standards set by an organization.